The pharmacokinetics of continuous subcutaneous levodopa/carbidopa infusion: Findings from the ND0612 clinical development program - LeWitt, Peter A.; Stocchi, Fabrizio; Arkadir, David; Caraco, Yoseph; Adar, Liat; Perlstein, Itay; Case, Ryan; Giladi, Nir (Frontiers in Neurology, 2022)
Background: While treatment with levodopa remains the cornerstone of Parkinson’s disease (PD) management, chronic oral therapy is often associated with the development of motor complications, that correlate to fluctuating levodopa plasma concentrations, limiting its clinical utility. Continuous infusion is considered to be the optimal delivery route for treating PD patients with motor fluctuations, but current infusion systems require invasive surgery. Subcutaneous infusion of (SC) levodopa has the potential to provide a better tolerated and more convenient route of continuous levodopa delivery. ND0612 is in development as a combination product providing continuous levodopa/carbidopa via a minimally invasive, subcutaneous delivery system for PD patients experiencing motor response fluctuations. We present pharmacokinetic results from a series of studies that analyzed plasma concentrations after SC levodopa delivery with ND0612 to inform the clinical development program. Methods: We performed a series of six Phase I and II studies to characterize the pharmacokinetics of levodopa and carbidopa derived from ND0612 infusion with/without adjunct oral therapy of the same ingredients. These studies were conducted in healthy volunteers and in PD patients experiencing motor response fluctuations while on their current levodopa therapy regimen. Results: Taken together, the results demonstrate dose-proportionality dependent on rate of subcutaneous levodopa infusion leading to stable and sustained plasma concentrations of levodopa. Subcutaneous infusion of ND0612 administered on top of standard of care oral levodopa/carbidopa maintained near-constant, therapeutic levodopa plasma concentrations, thereby avoiding the troughs in levodopa plasma concentrations that are associated with OFF time in PD. The data generated in this series of studies also confirmed that a levodopa/carbidopa dose ratio of 8:1 would be the most reasonable choice for ND0612 development. Conclusions: This series of clinical pharmacokinetic studies have demonstrated that ND0612, administered continuously with a levodopa concentration of 60 mg/ml combined with carbidopa 7.5 mg/ml, and complemented with oral levodopa/carbidopa, is suitable for 24 hours continuous administration in patients with PD. The stable plasma concentrations of levodopa achieved predict utility of ND0612 as a parenteral formulation for achieving clinically useful delivery of levodopa for PD patients.